Pengkhianatan Prinsip Keadilan Dalam Tindak Pidana Penggunaan Dokumen Palsu Pada Pemilihan Anggota DPRD - Evan Sammuelson Belvanio; Deni Achmad; Firganefi Firganefi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The act of falsifying documents in general elections is a serious violation of the basic principles of democracy and legal regulations governing the democratic process. In politics, document falsification not only impacts specific individuals or groups, but also substantially undermines the integrity and legitimacy of the democratic process as a whole. From a legal justice perspective, such actions violate the basic principles that should govern the integrity of elections, threatening the foundations of democracy itself. By using fake documents, individuals or groups can manipulate election results in unfair ways, leading to a reduction in public trust in democratic institutions. Moreover, such actions create doubts about the legitimacy and fairness of the election process, which is the main foundation of an effective democratic system. In the case mentioned, Dr. Sihabuddin Chalid, M.M., Pd. bin (late) Khalid Noor, deliberately created fake documents to become a candidate for DPRD members, which directly violated Law Number 7 of 2017 concerning General Elections. Therefore, strict law enforcement is very important to prevent abuse of political power and maintain public trust in government institutions.